Pyrolysis behaviour of sewage sludge produced at Sungai Udang central sewage treatment plant: article - Abd Rahim, Ain Adilla (2019)
Sewage sludge management become crucial issue now days as due to its poor managements the environmental as well as human health will be endangered. In order to overcome this issue various solutions were studied and thermochemical conversion is one of the most applicable solution for this problem. Other than large volume reduction, this method also converted the waste into valuable product such as fuel which then can be used to produce energy. Thermochemical conversion can be divided into three main process which are pyrolysis, combustion and gasification. In this study, the effect of temperature and composition of sewage sludge towards the pyrolysis behavior of the sludge were investigated. Proximate and Ultimate analysis were performed to determine the composition of sludge while pyrolysis behaviors were studied by Thermogravimetric Analysis (TGA). Sg. Udang Waste Water Treatment plant was chosen as the location for the sewage sludge collection. The sludge contains 38.6% volatile matter with only 6.14% moisture content after dried in conventional oven for 24hours. The carbon and hydrogen composition in the sludge were 15.2% and 2.57% respectively which make the H/C ratio is 2.1. Other than that, the main decomposition stage (main pyrolysis) of sewage sludge take place in the range temperature of 200⁰C – 500⁰C. The composition of liquid product produced from the condensation of condensable vapor were determined by GC/MS.